Corruption in Kazakhstan: and its impact on the economic development of the country - Abuova, М. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2020)
Corruption is a serious problem, and not only in developing countries. The fact is corruption interferes economic growth weakens the rule of law and underminesthe rule of law institutions.Moreover,ithasbeenstudiednationallyfromthedifferentperspectivesofthatissue. Recently,agrowingnumberofstudiesonlocalcorruptionand,theserecentstudieshavefocused on the corruption and its impact on voters. The report will consider corruption in the system of public administration in the Republic of Kazakhstan and will be focused on the consequences of the corruption on the economy of thecountry.